Crude oil recovery by new nonionic surfactants in relation to equivalent alkane carbon number (EACN) with work adhesion and alteration wettability - A. M. Al Sabagh; Ahmed I. Khodair; B. M. El-Sadek; Entsar E. Badr; Esraa Hamada Kalboush (Scientific Reports)
Abstract Six new nonionic surfactants abbreviated as (PMRH x), besides cationic surfactant ( RHATAS), based on ricinoleic hydrazide were prepared elsewhere. The nmin and alkane carbon number (ACN) at 50°C and concentration of CMC were determined by the n-hydrocarbon scans (n-c6 to n-c18) against the tension between n-c and surfactant solution. The work adhesion (Wa), surface charge energy, and spreading coefficient were calculated for these surfactants based on surface, interfacial tension, and measuring of contact angle. The rheological properties of the solution of these surfactants at CMC were measured at 50 °C to determine the dynamic (ηapp) and plastic viscosities (ηpl). Otherwise, the recovery factor of the crude oil was investigated by using a sand back model at 50 °C using waxy crude oil. The effect of ethylene oxide content in the surfactant structure was discussed via all the studied parameters. The surfactant PMRH 136 exhibited the maximum oil recovery (85.20%) individually, and its blend with RHATAS achieved a recovery factor (92%). A mechanism to describe the effect of these parameters on the recovery factor is introduced in the text.